A Case Report of Canine Histiocytic Sarcoma - Laoharatchatathanin, Titaree; Chareerat, Sasiprapha; Thermtong, Puttipong; Boonsriroj, Hassadin (Journal of Mahanakorn Veterinary Medicine, 2024)
An 8-year-old intact male mixed-breed dog present with a 2 month history of multiple subcutaneous nodules located on the dorsum, lateral thorax, ventral abdomen, and all four limbs and progressive exophthalmos of the right eye. Overall results from the general physical examination were normal unless depress vomit and right popliteal lymph node enlargement. Hematology revealed moderate non-regenerative anemia and leukocytosis. Thoracic radiology was unremarkable. Abdominal ultrasonography revealed marked enlargement of medial iliac and hepatic lymph nodes and found mass at retro-bulbar area. Fine-needle aspiration cytology of the skin mass and mass at retro-bulbar area revealed atypical cells of suspected malignant round cell tumor origin. Therefore, to confirm that type of cancer should be biopsy is performed for histopathological. Histopathological features of affected tissues composed of pleomorphic round cells arranged in closely packed sheets. The tumor cells were immunopositive for vimentin, CD204, and E-cadherin and negative for CD3. Based on the histopathological and immunohistochemical findings this case was diagnosed as canine histiocytic sarcoma.